The Economic Value Analysis of Aren Palm Tree in Goloketak, Boleng, West Manggarai District - Kurniawati, Liesiana; Savitri, Ni Wayan Noviana; Ratnaningsih, Ni Made Dwita (UTSAHA: Journal of Entrepreneurship, 2022)
This research is analyzed on aren palm tree in Goloketak, Boleng, West Manggarai District which aims to find out how many Goloketak people have used aren palm trees for economic benefits through the products they produce, these are sopi and palm sugar; and the possibility of developing economic value that has been obtained. The research sample was obtained from some people who produce sopi, palm sugar and other products from this aren palm tree which total of 28 respondents. The research method was conducted by interviewing 28 respondents. Based on the results of these interviews, it is known that most of the respondents use aren palm trees to produce only one product, it can be making sopi or making palm sugar and some people produce both. On the other hand, there are several respondents who produce other products such as palm fiber rope, palm  fiber brooms and roofing fibers based on orders only or for their own needs. The results of the interview indicated that using these aren palm trees has not been fully cultivated by the Goloketak people because most of sopi and palm sugar production comes from aren palm trees that grow themselves in their gardens. The income of the community from sopi drinks is IDR 48.152.632, and the income from palm sugar is IDR 28.701.842,- which is obtained from the average respondent per year.